2018
DOI: 10.3390/ijerph15061168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Perceived Risk of Middle East Respiratory Syndrome (MERS) in Korea

Abstract: The world is turning into a risky society. Although modernization based on the developments in science and technology has increased individuals’ well-being and wealth, the perceived risk toward the complex technological system has increased. In a risky society, social accidents amplify the existing fear among individuals. It is generally assumed that each value, perception, and resource influences the fear of risk. However, very few studies have tested these three factors together within an integrated causal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 50 publications
(92 reference statements)
2
69
1
8
Order By: Relevance
“…Interestingly, the knowledge score was higher in the non-physician group. Knowledge and years of experience could bring about positive attitudes that can be explained by the theory of reasoned action, which predicts that behavioral intent is caused by both attitudes and subjective norms [22,23]. Kim et al showed that knowledge, and not just trust, had an impact on the perceived risk of MERS [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the knowledge score was higher in the non-physician group. Knowledge and years of experience could bring about positive attitudes that can be explained by the theory of reasoned action, which predicts that behavioral intent is caused by both attitudes and subjective norms [22,23]. Kim et al showed that knowledge, and not just trust, had an impact on the perceived risk of MERS [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, according to Kuklinski et al [42], more knowledge engenders, more opposition toward the operation and construction of nuclear energy stations. Moreover, Kim and Kim [43] showed that more knowledge related to diseases decreases individuals' perceived risk of disease. A high knowledge lowers the perceived risk to a particular object, which in turn reduces the opposition behavior to it.…”
Section: H4mentioning
confidence: 99%
“…Many other studies investigate stress in the aftermath, which may not reflect the actual stress subjects felt during the actual event. Many publications addressed similar issues among hospital workers and residents; however, only a few studies investigate the psychological stress of university health college students during the MERS-CoV outbreak [4,5].…”
Section: Introductionmentioning
confidence: 99%